Pathogenic copy number variants are detected in a subset of patients with gastrointestinal malformations. Issue 2 (14th December 2019) - Winberg, Johanna; Gustavsson, Peter; Sahlin, Ellika; Larsson, Magnus; Ehrén, Henrik; Fossum, Magdalena; Wester, Tomas; Nordgren, Ann; Nordenskjöld, Agneta
Abstract: Background: Gastrointestinal atresias and urological defects are main causes of pediatric surgery in infants. As copy number variants (CNVs) have been shown to be involved in the development of congenital malformations, the aim of our study was to investigate the presence of CNVs in patients with gastrointestinal and urological malformations as well as the possibility of tissue‐specific mosaicism for CNVs in the cohort. Methods: We have collected tissue and/or blood samples from 25 patients with anorectal malformations, esophageal atresia, or hydronephrosis, and screened for pathogenic CNVs using array comparative genomic hybridization (array‐CGH). Results: We detected pathogenic aberrations in 2/25 patients (8%) and report a novel possible susceptibility region for esophageal atresia on 15q26.3. CNV analysis in different tissues from the same patients did not reveal evidence of tissue‐specific mosaicism. Conclusion: Our study shows that it is important to perform clinical genetic investigations, including CNV analysis, in patients with congenital gastrointestinal malformations since this leads to improved information to families as well as an increased understanding of the pathogenesis. Abstract : We detected pathogenic aberrations in 2/25 patients with gastrointestinal and urological malformation and report a novel possible susceptibility region for esophageal atresia on 15q26.3. CNV analysis in different tissues from the same patients did not reveal evidence of tissue‐specific mosaicism.